PWM current controller technique for Permanent Magnet Synchronous Motor speed control at constant torque / Izzati Abd Halim - Abd Halim, Izzati (2001)
This paper presents the application of Pulse Width Modulation (PWM) current controller technique applied to Permanent Magnet Synchronous Motor (PMSM). The speed is varied constant torque. The first part of the paper presents the analysis of PWM to determine the right parameter.